If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6u + -1w = u + -4w Solving 6u + -1w = u + -4w Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-1u' to each side of the equation. 6u + -1u + -1w = u + -1u + -4w Combine like terms: 6u + -1u = 5u 5u + -1w = u + -1u + -4w Combine like terms: u + -1u = 0 5u + -1w = 0 + -4w 5u + -1w = -4w Add 'w' to each side of the equation. 5u + -1w + w = -4w + w Combine like terms: -1w + w = 0 5u + 0 = -4w + w 5u = -4w + w Combine like terms: -4w + w = -3w 5u = -3w Divide each side by '5'. u = -0.6w Simplifying u = -0.6w
| 3x-4y=16ni | | 35=(2w+3)w | | 6-6x=5-2x-64-4x | | 10x^2+88x=88 | | 7x+9y=142506 | | -7(-3+6d)-(2-6h)(-6)= | | (5+4)lnk=12 | | K+20=9k(-4) | | 15uv+32-40u-12=0 | | 206+8logx=190 | | (19b-3)-6(3b+4)=-3 | | 4cosx-5sin^2x=3 | | 51b-b= | | 4x-6x+12=12 | | 5+4ln(k)=12 | | 9x^2+30=36z | | 6(2n+1)=6(8n+5)+7 | | 2y-5=-20 | | -3p+2p= | | 5y^2=-7y-2 | | -2x=-3x^3-2 | | -5x+7x+16=11x-3-x | | x^3-5x+2x^2-10=0 | | 180-(7x-12)=5x | | -2(3t-4)+3t=5t-7 | | x+120=40 | | 5y+9=-2y+3 | | x-4y=y^2+7 | | 2y-5x=-20 | | 7x=-4x-3 | | 4y-11+5= | | -5(2t-3)+8t=7t-5 |